Pemalsuan Mata Uang Sebagai Kejahatan Di Indonesia - Agus Arif Wijayanto (UNISSULA Semarang, 2020)
A crime of money forgeries in Indonesia has been categorized into two subjects which is imitating the money and distributing the counterfeit. The regulation about it is penalty arranged in the Rule Number 7 on 2011 about The Law of Currency. The distribution of counterfeit money in Indonesia occurs because there are a lot of people who have a below average income. Another factor is the misapplication of technological advances. Thus, the Government of Indonesia is being expected for making a revision within the regulation about The Currency with publishing it is own punishment and the minimum fine in order to make the purposes of the punishment becoming more effective that is for causing a deterrent effect to making it achieveable. Beside that, The Law Enforcer must be more honouring the professionalism in carrying out it is role and job within the effort of Law Enforcement against Counterfeiting cash crime in Indonesia. Key Word: Counterfeiting, The Currency, Crime